PENGARUH PERMAINAN BLOCK PUZZLE EDUKATIF TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI ANAK USIA 5-6 TAHUN DI RA AL-HIDAYAH KOTA PEKANBARU - Diah Ayu Rahmadini; Ria Novianti; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of educational block puzzle games on the ability to recognize geometric shapes of children aged 5-6 years in RA Al-Hidayah, Pekanbaru city. The population in this study were children aged 5-6 years in RA Al-Hidayah, Pekanbaru City, amounting to 20 people, the sample of this study was 20 people. The method used is the One Group Pre-test-Post-test design to see the influence of the variable educational block puzzle games on the ability to recognize geometric shapes. Data collection techniques used are observation. Data analysis techniques using linearity test, homogeneity test, normality test, correlation test and hypothesis testing with SPSS for Windows Ver. 12. Based on the results of the hypothesis test obtained there is a positive and significant influence between the educational block puzzle games on the ability to recognize geometric shapes in children aged 5-6 years in RA Al-Hidayah, Pekanbaru city. This can be seen from the hypothesis value of t = 34,550 and the significance level of 0.00 <0.05. The effect of educational block puzzle games on the ability to recognize geometric shapes in children is included in the medium category with the value of the centralized gain generated at 54,83%, meaning that the postbox game has an effect of 54,83% on the ability to recognize geometric shapes.Key Words: Geometry Form, Educational Block Puzzle Game